Discrete Mathematics and its applications - Rosen, Kenneth H. (Boston, 2008)
The discrete mathematics course has more than one purpose. Students should learn a particular set of mathematical facts and how to apply them; more importantly, such a course should teach students how to think logically and mathematically. To achieve these goals, this text stresses mathematical reasoning and the different ways problems are solved.
Keywords: Discrete Mathematics